Uma ontologia evolucionista: considerações sobre a noção de "desenvolvimento" na obra de Darcy Ribeiro - Moreira, João Paulo Aprígio (2012)
This work investigates possible relations between a modern anthropological theory and discourses about "development". These relations are presented in theories of cultural change which will be consider with focus on the role mediators play in the production of specific meanings to the notion of "development". The analysis focus on Darcy Ribeiro´s 'The Civilizing Process: stages of sociocultural evolution', published in 1968. In thhis book Ribeiro presents his theory articulating a neoevolucionist anthropological perspective with a project of development for the Brazilian nation based on the concept of "technological revolutions". This concept is one of the foundations of Ribeiro's idea of cultural change at the same time offers a critique of dependency theory in Latin America, in the form of placing in th epolitical field debates on the underdevelopment-"Development" constrast. From the concept of technological revolutions, Ribeiro returns to the issue of cultural dynamics, dear to the theories of modern anthropology and grounded in an evolutionary perspective, as well as to the values of the national-developmentalism defended by Labour politicians - values that reside in the critical dependence of Latin countries' economic and the search for political autonomy, as well as in the defense of nations "underdeveloped" as the path to development.